Newton's cradle: Cell cycle regulation by two mutually inhibitory oscillators - Dragoi, Calin-Mihai; Tyson, John J.; Novák, Béla (Mathematical biosciences, 2024)
•Two doubly amplified, negative feedback oscillators control the cell division cycle.•They drive alternating phases of chromosome replication and segregation.•Mutual inhibition between the two oscillators is responsible for their alternation.•Arrest of one oscillator may lead to endocycles or to checkpoint arrest of the cycle.•A ‘toy’ model (4 ODEs) captures all essential dynamical features of the cell cycle. The cell division cycle is a fundamental physiological process displaying a great degree of plasticity during the course of multicellular development. This plasticity is evident in the transition from rapid and stringently-timed divisions of the early embryo to subsequent size-controlled mitotic cycles. Later in development, cells may pause and restart proliferation in response to myriads of internal or external signals, or permanently exit the cell cycle following terminal differentiation or senescence. Beyond this, cells can undergo modified cell division variants, such as endoreplication, which increases their ploidy, or meiosis, which reduces their ploidy. This wealth of behaviours has led to numerous conceptual analogies intended as frameworks for understanding the proliferative program. Here, we aim to unify these mechanisms under one dynamical paradigm. To this end, we take a control theoretical approach to frame the cell cycle as a pair of arrestable and mutually-inhibiting, doubly amplified, negative feedback oscillators controlling chromosome replication and segregation events, respectively. Under appropriate conditions, this framework can reproduce fixed-period oscillations, checkpoint arrests of variable duration, and endocycles. Subsequently, we use phase plane and bifurcation analysis to explain the dynamical basis of these properties. Then, using a physiologically realistic, biochemical model, we show that the very same regulatory structure underpins the diverse functions of the cell cycle control network. We conclude that Newton's cradle may be a suitable mechanical analogy of how the cell cycle is regulated. [Display omitted]